Beginning programming with Python for dummies - Mueller, John, 1958- (--For dummies., 2014)
Learn Python-the fun and easy way-and get in the programming game today! Python is one of the fastest growing programming languages, and no wonder. It requires three to five times less time than developing in Java, is a great building block for learning both procedural and object-oriented programming concepts, and is an ideal language for data analysis. Beginning Programming with Python For Dummies is the perfect guide to this dynamic and powerful programming language-even if you''ve never coded before! Author John Paul Mueller draws on his vast programming knowledge and experience to guide yo.